The influence in the Digital Environment: : the dynamics of Social Influence Strategies on Instagram (Comunicação & Inovação, 2023)
The communicative interactions and social relationships promoted by digital influence (DI) are processes of social influence (SI). These processes explain the mechanisms that can affect the attitudes and beliefs of individuals or groups. In this context, identifying the predominant strategy of SI and its dynamics can reveal mechanisms for structuring the message and the communication plan. This research is qualitative and exploratory; the data collection instrument is the Attitude Scale, Likert-type, applied to users of Instagram social network. The data suggest that the DI-mediated communicative interaction establishes SI strategies with a deliberate preference for social change strategies for collective (dynamic) action, whose predominance is the Conversion Strategy.
Keywords: Communication; Consumption; Digital Influence; Social influence; Strategies